Implementation of Sustainable Management-Based Design Thinking to Reduce Flower Board Waste in Higher Education - Sabrinadiza Balya; Elina Sabella Ambari; Annisa Rachmah; Asep Taryana (Al-Qalam Institue, 2025)
Universities pursuing Green University status often face a critical conflict between sustainability mandates and the deep-seated cultural tradition of receiving floral boards (papan bunga), which generates massive, unmanageable waste. This study applies the Design Thinking methodology to resolve this cultural-environmental conflict at a state university in South Tangerang. Through the Empathize and Define stages, the study identified that the root problem lay not in waste management, but in the cultural habit of sending physical tokens. Consequently, the Ideate phase formulated a